Cultural diversity and leadership styles in Malaysia’s corporate sector - Vallasamy, Suriya Kumareswaran; Chandrapragasan, Elilen; Muthu, Harivanandan; Subramaniam, Kartig; Nair, Deepakk (Intelektual Pustaka Media Utama, 2024)
In an era marked by globalization and heightened competition, this study delves into how sociodemographic factors such as age, gender, education, and work experience influence leadership styles, crucial for achieving organizational objectives. Employing the leadership behaviour questionnaire on 336 predominantly educated, male professionals of Indian descent in Malaysia's corporate sector, the research evaluates task and relationship orientations in leadership. The findings highlight a significant prevalence of both task-oriented and relationship-oriented leadership behaviours. Intriguingly, there is a positive correlation between higher education, age, work experience, and relationship orientation, while education and salary predominantly affect task-oriented leadership. A notable discovery is the positive interplay between task and relationship orientations, suggesting their complementary nature. The study concludes that a balanced, multifaceted leadership approach, fostering both efficiency and employee welfare, is vital. It underscores the impact of educational and professional growth on leadership skills and the necessity of diverse leadership styles for optimal organizational performance, offering key insights for leadership development in varied settings.